Atrial fibrillation and microRNAs - Santulli, Gaetano; IACCARINO, Guido; De Luca, Nicola; Trimarco, Bruno; Condorelli, Gianluigi (Frontiers in Physiology, 2014)
Atrial fibrillation (AF) is the most common sustained arrhythmia, especially in the elderly, and has a significant genetic component. Recently, several independent investigators have demonstrated a functional role for small non-coding RNAs (microRNAs) in the pathophysiology of this cardiac arrhythmia. This article represents a systematic and updated appraisal of the studies that established a mechanistic association between specific microRNAs and AF, focusing both on the regulation of electrical and structural remodeling of cardiac tissue.